Preoperative predictors of early relapse/no‐remission of type‐2 diabetes after metabolic surgery in Chinese patients. Issue 2 (7th January 2020) - Nautiyal, Hemant K.; Guan, Wei; Lin, Shibo; Liang, Hui
Summary: Remission of type 2 diabetes mellitus (T2DM) after metabolic surgery in some patients is not sustained. There is limited data regarding the preoperative factors predicting early relapse of T2DM in Chinese patients. The objective of this study is to look for preoperative predictors of early T2DM relapse/no remission in patients with obesity and diabetes who underwent Roux‐en‐Y gastric bypass (RYGB) or loop duodeno‐jejunal bypass with sleeve gastrectomy (LDJB‐SG). This is a retrospective study of 113 patients who underwent RYGB or LDJB‐SG for T2DM. All T2DM patients with BMI 27.5 to 37.5 kg/m 2, having uncontrolled diabetes and T2DM patients with BMI > 37.5 were included in the study. A multivariate analysis with a logistic regression model was used for analysed factors. Nineteen patients (16.8%) had early relapse and 12 (10.6%) did not have remission. Mean age of patients was significantly more who relapsed/no‐remission (44.9 vs 40.3 years). On univariate analysis, base line weight (86 vs 96.7 kg) was significantly lower in patients who relapsed/no‐remission. Patients with sustained remission had statistically significant low glycosylated haemoglobin ( P  < .030), plasma glucose (120 minutes) ( P  < .002) on OGTT, area under curve glucose ( P  < .011) values and more C‐peptide ( P  < .006) on univariate analysis. Only duration of diabetes (OR 2.78, 95% CI 1.56‐4.97, P  < .001) was found to be independent preoperative factor associated with early relapse/no‐remission. Two years of diabetes duration was the cut‐off point to predict relapse/no‐remission (sensitivity 78.9, specificity 63.4, receiver operating characteristic curve 0.71). Duration of diabetes is the most probable, independent preoperative predictor of early T2DM relapse/no‐remission in patient with obesity and diabetes undergoing metabolic surgery.